(untitled) (Journal of Comparative & International Higher Education, 2024)
While student mobility is increasingly important for HEIs, most research has focused on international mobility, what is commonly referred to as study abroad or education abroad. Arguing for expanding our understanding of mobility practices, this qualitative research study explores the lived experiences of participants in a domestic study away program to Hawaiʻi. The voices of individual participants were contextualized by consciously foregrounding and centering the specificity of place - Hawaiʻi - and its manufactured tourist gaze. The findings indicate that participants experience Hawaiʻi as foreign and familiar, and they negotiate being both students and visitors. Not wanting to be thought of as tourists, participants emphasized the importance of being respectful while on exchange, and many demonstrated that by taking courses which focused specifically on Hawaiʻi. As a result of these classes, many participants were able to develop a more complicated and nuanced understanding of Hawaiʻi which troubled notions of this place as paradise.